Utilizing Universal Design For Learning in Differentiated Learning at Inclusive Elementary Schools: A Qualitative Case Study - Hasanah Rosidah; Minsih Minsih (FKIP - Universitas Riau, 2026)
Inclusive elementary education requires instructional approaches that accommodate diverse student needs, particularly for learners with special needs. This study aims to determine the utilization of Universal Design for Learning in differentiated learning at SD Muhammadiyah PK Baturan and to analyze its impact on students with special needs' participation and the quality of their learning experience. This study used a qualitative approach with a case study design. Data and data sources were collected from classroom teachers, regular students, and students with special needs. Data collection was conducted through interviews, observations, and documentation. Data validity was ensured through triangulation. Data analysis was conducted inductively, including data reduction, data presentation, and conclusion drawing. The results showed that the utilization of Universal Design for Learning in differentiated learning was proven to (1) improve accessibility, (2) participation, and (3) learning experiences for students, including students with special needs, through flexible, humanistic strategies that reduced learning barriers. The conclusion of this study is that the integration of Universal Design for Learning into differentiated instruction is an effective and sustainable approach to strengthening inclusive education practices in elementary schools.